Une affaire lyonnaise : la succession de l’abbé Couturier - Étienne Fouilloux (Chrétiens et Sociétés, 2012)
The Abbot Paul Couturier pioneer of "spiritual ecumenism" died in Lyon in march 1953. Then his collaborators divided on the new forms they could give to a work so marked by the personality of its founder. Whereas Maurice Villain and Victor Carlhian wished to preserve its diocesan roots, the Dominicans Fathers Biot and Beaupère intended to favour the theological approach. So two catholic approaches of Ecumenism are implemented in Lyon : the Dominican Maurice-René Beaupère founded Saint-Irénée’s centre and the Sulpician Pierre Michalon founded the Centre for Christian Unity with Archbishop Gerlier’s support. Between 1951 and 1955, the study of Paul Couturier’s succession refers to three major debates going threw French Catholicism : the respective role of the prayer for unity and the theological work in the emergence of ecumenism on catholic ground ; a certain mistrust from the secular clergy toward Friars multiplying the initiatives in the outposts of the Church of France ; Lyon’s will to preserve the primature of the Gauls’influence by avoiding the initiatives raised in Lyon could be taken up by Paris.